THE INFLUENCE OF WORK MOTIVATION, WORK DISCIPLINE, AND WORK LOYALTY ON PT EMPLOYEE PERFORMANCE PT. AGGIOMULTIMEX INTERNATIONAL GROUP IN SIDOARJO - Ali, Mukti; Lusiana, Silvy (Ecopreneur.12, 2025)
The ability of a company to achieve success lies not only in its human resources, but also in how well its people behave and the performance of employees to achieve goals quickly and effectively. This research aims to determine the influence of work motivation and discipline work, and work loyalty on the performance of PT employees. Aggio multimex International Group in Sidoarjo. The research method used in The research is a quantitative method with linear regression analysis techniques, tests classical assumptions, reliability test, validity test, T test, F test, R determinant coefficient test by using the SPSS Version 26 test tool to manage the data. The population in this study were employees of PT. Aggiomultimex International Group sewing department totaling 85 employees. The sampling technique in this study used saturated samples, so that a sample of 85 employees was obtained. The results of the study indicate that work motivation partially has a positive effect on performance (t-count value 2.095 > t-table 1.999), work discipline partially has a positive effect on performance (t-count 2.242 > t-table 1.999), work loyalty partially has a positive and significant effect on performance (t-count 5.043 > t-table 1.999) and simultaneously the variables of work motivation, work discipline, and work loyalty have a positive and significant effect on employee performance (f-count 43.859 > f-table 2.717).